Análises da arritmia sinusal respiratória - Ladeira, Guênia Mara Vieira (2020)
Heart rate variability is essential for maintaining the homeostatic balance of the body. It is controlled by the autonomic nervous system. Human biological systems have standard basic characteristics, but varieties of construction and functioning due to genetics, age, sex, and also disease impairment. In addition, they have a complex relationship between systems, such as the nervous system and the cardiorespiratory system. Further analysis of a complex system reveals causes and consequences of its functioning, and helps to detect problems and solve them. Motivated by a better understanding of this relationship I will deepen the analysis of the systems to contribute to the research in this area. The efficiency of the autonomic regulation can be verified by means of respiratory sinus arrhythmia tests observed through electrocardiogram signals ECG and the response of the nervous system can be perceived by electroencephalogram EEG. In this work I present some approaches in the analysis of complex systems such as biological ones. The most relevant contributions of the research are prepared from the knowledge of the cardiorespiratory and nervous biological systems, and the direct relationship between them. The work was concerned with the quality of the instrumentation for biological signal collection and pre-processing for analysis. This stage generated the construction of electrocardiogram equipment. Then, ECG signals were collected from the paralympic boccia team, while the athletes performed their usual breathing exercises to improve concentration and alter heart rates. The electrocardiograms were analysed through the techniques of quantification of recurrence observing the details of the alterations during the exercises. Another approach of the research was the mathematical models of the electrocardiogram. The ECG models were studied and the Kaplan oscillator was chosen, whose model was analysed through bifurcation diagrams and improved in its results. How the athletes change the pattern of the heart and increase the concentration with the exercises. The work passed the EEG analysis stage. Several analyses were performed by linear and non-linear techniques, comparing the signals between the participant with open eyes and closed eyes. A new recurrence analysis technique in the frequency spectrum was generated in this part. The technique presented relevant results to better characterize the signals, can be used to characterize case of depression, and other diseases affecting the central nervous system. Data collection in set of ECG and EEG performing the breathing exercise were performed, the data were analysed by already established techniques and by the recurrence technique created here, we showed that there is a relationship between the heart and brain signals in performing the breathing exercises. All the stages of the work have generated articles which have been published, the first in congresses and the last in specialized journals.